INNOVATIVE APPROACHES TO IMPROVING THE QUALITY OF EDUCATION THROUGH TEACHING PHILOLOGY - Boboeva Bakhora (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In today's rapidly changing world, traditional teaching methods are no longer effective in providing students with the skills and knowledge they need to succeed. This is especially true in the field of philology, where innovative approaches to teaching are necessary to keep up with the demands of modern society.